A contribution for the quantification of the influence of windows on the airtightness of Southern European buildings - Almeida, Ricardo (2017)
Adequate airtightness levels are fundamental for the indoor environmental quality and energy efficiency of buildings. The quantitative characterization of expected leaks of common building elements is useful for practitioners that intend to improve building enclosures for airtightness optimization. This study intends to contribute to the quantification of the permeability of windows with a focus on the Southern European context of low airtightness in heavy construction buildings, where windows play an important role. A large experimental investigation was therefore carried out in 23 spaces, establishing three possible set-ups (nothing sealed, window sealed and window and roller-shutter sealed), using the fan pressurization method. A total of 104 tests were performed. Results revealed that the windows’ permeability indices ranged from 4.8 to 96.4 m3/(h m2) and from 1.2 to 30.8 m3/(h m), with average values of 28.7 m3/(h m2) and 8.9 m3/(h m), the roller-shutter contribution can be highly variable; also the year of construction, the frame material and the opening system are the key parameters for the airtightness of windows